2008
DOI: 10.1179/016164107x228697
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and induction of differentiation by panaxydol in rat C6 glioma cells

Abstract: These findings suggest that panaxydol inhibits the proliferation of C6 cells via G0/G1 cell cycle arrest in association with induction of p27 expression and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Essentially, falcarinol eliminated CSC population in NSCLC and abolished lung tumor formation in mice via HSP90 (a molecular chaperone of numerous oncoproteins) modulation [302]. Falcarinol anticancer activity also extends to leukemia [303], breast cancer [304], hepatocarcinoma [305], renal carcinoma [306], and glioma [307]. For instance, mechanisms pointed to explain its ability to induce cell cycle arrest, thus, its anticarcinogenic properties on human promyelocytic leukemia cell growth are PKCδ proteolytic cleavage, caspase-3 activation, and PARP degradation [303].…”
Section: Falcarinolmentioning
confidence: 99%
“…Essentially, falcarinol eliminated CSC population in NSCLC and abolished lung tumor formation in mice via HSP90 (a molecular chaperone of numerous oncoproteins) modulation [302]. Falcarinol anticancer activity also extends to leukemia [303], breast cancer [304], hepatocarcinoma [305], renal carcinoma [306], and glioma [307]. For instance, mechanisms pointed to explain its ability to induce cell cycle arrest, thus, its anticarcinogenic properties on human promyelocytic leukemia cell growth are PKCδ proteolytic cleavage, caspase-3 activation, and PARP degradation [303].…”
Section: Falcarinolmentioning
confidence: 99%
“…Cells treated with 60 lM panaxydol for 48 h were therefore used for subsequent experiments. 7,11 Briefly, 2.5 Â 10 3 C6 cells were seeded in 96-well microtiter plates (Nune, Roskilde, Denmark), incubated at 37°C for 24 h, and grown with or without 5 lM wortmannin for 4 h; 60 lM panaxydol was added to the medium. Cells were harvested after 48 h. MTT (10 lL) was added to each well, and cells were incubated at 37°C for 4 h. Absorbance at 570 nm was read on a microplate reader against a reference wavelength of 630 nm.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…These aliphatic C17 polyacetylenes were isolated from the lipophilic fractions of a well-known herb in Chinese traditional medicine, Tienchi ginseng (Panax notoginseng). [7][8][9] The molecular mechanisms underlying this differentiation are unknown. In this study, we propose that PI 3-K activity is required for the regulation of differentiation in C6 cells treated with panaxydol.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, agents extracted from Chines traditional medicine have been reported to have therapeutic effects against gliomas. For examples, Jian et al reported that panaxydol, isolated from the lipophilic fractions of Panax notoginseng, a well-known Chinese traditional medicine, inhibited the proliferation of C6 cells in a dose-dependent manner and induced p27 expression and differentiation in rat C6 glioma cells [6]. Shao et al reported that nanoparticles loaded with Curcumina, yellow pigment in the spice turmeric displayed pro-apoptosis effect against C6 cells [7].…”
Section: Introductionmentioning
confidence: 99%